2021
DOI: 10.1172/jci.insight.146316
|View full text |Cite
|
Sign up to set email alerts
|

A majority of uninfected adults show preexisting antibody reactivity against SARS-CoV-2

Abstract: Pre-existing cross-reactivity to SARS-CoV-2 may occur in absence of prior viral exposure. However, this has been difficult to quantify at the population level due to a lack of reliably defined seroreactivity thresholds. Using an orthogonal antibody testing approach, we estimated that 0.6% of non-triaged adults from the greater Vancouver area, Canada between May 17 th and June 19 th 2020 showed clear evidence of a prior SARS-CoV-2 infection, after adjusting for false-positive and false-negative test results. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 30 publications
7
40
3
Order By: Relevance
“…Findings are in keeping with modelling studies 31,32 and data from the UK where low seroprevalence was also measured in teachers, but this was earlier in the pandemic 15 . Moreover, despite that the seroprevalence in this study represents an approximately threefold increase relative to previous estimates of 0.55% to 0.6% obtained from Vancouver residents in spring 2020 [33][34][35] , it remained comparable to age/sex and area of residency-matched blood donors.…”
Section: Discussioncontrasting
confidence: 94%
“…Findings are in keeping with modelling studies 31,32 and data from the UK where low seroprevalence was also measured in teachers, but this was earlier in the pandemic 15 . Moreover, despite that the seroprevalence in this study represents an approximately threefold increase relative to previous estimates of 0.55% to 0.6% obtained from Vancouver residents in spring 2020 [33][34][35] , it remained comparable to age/sex and area of residency-matched blood donors.…”
Section: Discussioncontrasting
confidence: 94%
“…Overall, with this small sample of sera there was little difference between the patterns of reactivity of the sera from the sick and healthy groups. This high detection of anti-spike and anti-nucleocapsid immunoreactivity in serum samples from healthy individuals is consistent with previous studies using two different serological tests developed by Mesoscale Devices and Kinexus (31).…”
Section: Cbm9-sars-cov-2 Fusion Proteins React With Rabbit Anti-spike Protein Sera and Human Serasupporting
confidence: 92%
“…The absence of IgA2 antibodies specific for SARS-CoV-2 antigens in severely diseased COVID-19 patients has also been demonstrated [8], suggesting that mucosal anti-viral IgA antibodies may protect the host from a severe course of COVID-19. Several studies have reported the presence of RBD-binding antibodies in unexposed healthy individuals [9,10,11,12,13].…”
Section: Main Textmentioning
confidence: 99%